EUROPEAN AND NON EUROPEAN IN UNIVERSAL GEOGRAPHY SCHOLAR HANDBOOKS, COLOMBIA 1970-1990 - Cerón Rengifo, Carmen Patricia (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2012)
The scholar geography handbooks  express an idelogical speech on population organized under the intelectual operations of the Eurocentrism. With the objective of exploring the representation of the popualtion  promoted as an oficial knowledge of social studies, universal geography scholar handbooks samples were published in Colombia between 1970 and 1990; they were addressed to eighth students of highschool. As a methodological  guideline, a follow –up was carried out to the positive representation of us and negative of others, the tools were taken from Van Dijk (2008). According to Quijano (2000, 2003), it is concluded that  Euroean, Asian, African and Oceania population are classified into a hierarchical way by means of the race idea; it is established a semantic polarization between European and non european (civilized/ primitives, modern and traditional,  developed /underdeveloped) and it is located temporarily in the non European as the past of the historical trajectory  ending up in Europe.